Collaborative Processes in Science and Literature: an In-Depth Look at the Cases of CERN and SIC - Leogrande, Emilia; Nicassio, Renato (Frontiers in Research Metrics and Analytics, 2021)
In this paper we examine how the process of collaboration works in science and literature. In the first part, we discuss the features of scientific collaboration and literary collaboration and the differences between them. In the second part, we analyze two processes of collaboration, each from a different field:  the case of CERN and high-energy physics and the case of Scrittura Industriale Collettiva and its Great Open Novel. Lastly, we try to compare those two processes and deduce the common traits of a successful collaboration.